A fill-in-blank problem workbook for Java programming learning assistant system. Issue 2 (19th June 2017) - Na, Ta; Funabiki, Nobuo; Zaw, Khin Khin; Ishihara, Nobuya; Matsumoto, Shinpei; Kao, Wen-Chung
Abstract : Purpose: To advance Java programming educations, the authors have developed a Java Programming Learning Assistant System (JPLAS) as a web application system. JPLAS provides fill-in-blank problems for novices to study the grammar and basic programming skills through code reading. Design/methodology/approach: To select the blank elements with grammatically correct and unique answers from a given Java code, the authors have proposed the graph-based blank element selection algorithm. Then, the code for this problem should be highly readable to encourage novice students to study it. Because code readability can be improved by proper names for identifiers, the authors have also proposed the naming rule testing algorithm to identify codes with correct names. Findings: In this paper, the authors present a fill-in-blank problem workbook by collecting suitable Java codes from textbooks and Web sites and applying these algorithms with several extensions. The workbook consists of 16 categories with a considerable number of problems that follow the conventional learning order of Java programming. Originality/value: The proper set of ready-made fill-in-blank problems is effective in enhancing the usability of JPLAS both for teachers and students. For the preliminary evaluation, the authors assign a few problems to students. In coming semesters, the authors will use this workbook in the course to verify the adequacy of the proposal for novices.